Nonlinear Transmission Optimization Design of the Mechanical Aircraft Engine Control System - Luo Yunhe; Zeng Xiaojie; Zhao Zheng (Jixie chuandong)
Nonlinear transmission by special mechanism has been applied in the mechanical flight control system. Through approximate fitting of transmission requirements, the design parameters of the mechanism can be solved. The mechanism designed by this method cannot accurately fulfill the transmission constraint condition, so it has not been applied in the mechanical aircraft engine control system. Based on the characteristic of the mechanical aircraft engine control system, the four-bar mechanism is substituted by the five-bar mechanism to realize nonlinear transmission. The mechanism design parameters are divided into optimization decision parameters and transmission control parameters by analyzing the principle of five-bar mechanism design parameters, the mechanism solving method and optimization design method are built to directly solve the mechanism design parameters and make the transmission characteristic fulfill the constraint condition precisely. Then the maximum transmission ratio and mechanism wear factor are used as the objective function to optimize the mechanism design to improve system performance and service life. Furthermore, it is proved by the engine control system design example and ground test that this method is reasonable and practicable with practical value in engineering.